The tectono-stratigraphic evolution of Eastern Mediterranean with emphasis on Herodotus Basin prospectivity for the development of hydrocarbon fields - Elia, C.; Konstantopoulos, P.; Maravelis, A.; Zelilidis, A. (Bulletin of the Geological Society of Greece, 2013)
The eastern part of the Mediterranean Sea is of great geological interest. One of the main interesting topics is the genesis and the development of hydrocarbon fields in the area. The analysis of the palaeogeographic evolution of two major basins in eastern Mediterranean Sea, such as Levantine basin and Herodotus basin, shows the same evolution and accommodate the same sediment types. Also, the presence of the Eratosthenes Continental Block (E.C.B.) and the Nile cone, have their own role in the development of the basins and the wider Eastern Mediterranean region. With the help of seismic data, petroleum geology, the evolution of both basins and other geological structures of the region, we can compare the two basins. From the comparison we concluded that Herodotus basin hosts at least the same amount of gas and oil as the Levantine basin.